Competition stress in sport performers: Stressors experienced in the competition environment - Mellalieu, S. D.; Neil, R.; Hanton, S.; Fletcher, D. (Journal of Sports Sciences, 2009)
We examined the performance and organizational stressors encountered by elite and non-elite athletes within the competition environment. Twelve sport performers (6 elite, 6 non-elite) were interviewed about both performance and organizational-related demands experienced when preparing for competition. The framework presented identifies five performance (i.e. preparation, injury, expectations, self-presentation, and rivalry) and five organizational (i.e. factors intrinsic to the sport, roles in the sport organization, sport relationships and interpersonal demands, athletic career and performance development issues, and organizational structure and climate of the sport) stress sources. A similar quantity of performance (#PS) and organizational (#OS) stressors were encountered by elite performers (#PS = 127; #OS = 72) as by non-elite athletes (#PS = 123; #OS = 74), with some demands being common and others unique to each group. Although the findings suggest that, prior to competing, sport performers encounter more stressors pertinent to performance than those emanating from the organization, these observations highlight that all the demands faced by athletes should be considered when preparing and implementing interventions to manage competition stress.